THE EFFECT OF JOB DESCRIPTION AND JOB SPECIFICATION ON EMPLOYEE PERFORMANCE AT PT QIBLATAIN SAKTI - Basofitrah, Achmad; Hayeh, Nur (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
With very tight business competition in the current era, the role of job descriptions and job specifications has become very important for the progress of a company, because it can help employees improve their performance in carrying out their duties. Based on the results of research conducted on PT Qiblatain Sakti employee respondents, it was found that the implementation of job descriptions is still very low, which can hinder the company's progress. Therefore, companies need to improve the implementation of job descriptions and job specifications to achieve the targets that have been set. This research uses quantitative methods with data obtained from employee respondents of PT Qiblatain Sakti, which is then explained descriptively qualitatively so that it is easy for readers to understand.